Innovation Packaging and Scaling Readiness (IPRS) Workshop Report on socio-technical innovation bundling - Nyamolo, Victor; Lutomia, Cosmas K.; Buono, Nicoletta; Ketema, Dessalegn; Gartaula, Hom; Waswa, Boaz; Puskur, Ranjitha; Nchanji, Eileen (2024)
The Socio-Technical Innovation Bundling Packaging and Scaling Readiness (IPRS) Workshop, held in Nairobi on May 28, 2024, was organized to analyse and enhance the scaling potential of Socio-Technical Innovation Bundles (STIBs). The workshop aimed to equip participants with a deep understanding of STIBs and to share key insights from the CGIAR Gender Equality Initiative (HER+) research conducted in Kenya in collaboration with the Initiative on Diversification for East and Southern Africa. Participants explored strategies for scaling STIB innovations, ensuring they can be replicated across different regions and contexts, creating impacts in empowerment, resilience, nutrition and food security. The workshop highlighted the need for STIBs and their role in addressing complex socio-technical challenges and positive impacts. Discussions focused on identifying effective pathways for integrating STIBs into national and international agricultural programs, as well as the initiatives of development agencies. The workshop aimed to strengthen existing partnerships and foster new ones among stakeholders, gathering valuable feedback to refine the design and implementation of STIBs. The workshop concluded with actionable recommendations for integrating and scaling STIBs within agricultural programs, development initiatives, and other relevant sectors. These efforts are expected to enhance climate resilience, promote gender equality, and empower African and Asian communities.